2015
DOI: 10.1016/j.neuroimage.2015.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Normative development of ventral striatal resting state connectivity in humans

Abstract: Incentives play a crucial role in guiding behavior throughout our lives, but perhaps no more so than during the early years of life. The ventral striatum is a critical piece of an incentive-based learning circuit, sharing robust anatomical connections with subcortical (e.g., amygdala, hippocampus) and cortical structures (e.g., medial prefrontal cortex (mPFC), insula) that collectively support incentive valuation and learning. Resting-state functional connectivity (rsFC) is a powerful method that provides insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 179 publications
(290 reference statements)
9
70
1
Order By: Relevance
“…These findings have at least two possible explanations. One explanation is that developing neurobiology allows for prefrontal regulation of subcortical structures involved in generating appetitive responses before regulation of regions involved in generating aversive responses (see Fareri et al, in press; Gabard‐Durnam et al, ). Another possible explanation is that children have more experience interpreting food cues than they do with negative social situations and this experience facilitates better regulation (i.e., children eat food every day of their lives but encounter negative social situations less frequently).…”
Section: The Person By Situation By Strategy Modelmentioning
confidence: 99%
“…These findings have at least two possible explanations. One explanation is that developing neurobiology allows for prefrontal regulation of subcortical structures involved in generating appetitive responses before regulation of regions involved in generating aversive responses (see Fareri et al, in press; Gabard‐Durnam et al, ). Another possible explanation is that children have more experience interpreting food cues than they do with negative social situations and this experience facilitates better regulation (i.e., children eat food every day of their lives but encounter negative social situations less frequently).…”
Section: The Person By Situation By Strategy Modelmentioning
confidence: 99%
“…The amygdala has strong bidirectional projections with the PFC (Barbas, Saha, Rempel-Clower, & Ghashghaei, 2003), while the ventral striatum receives unidirectional projections from the amygdala and PFC, including excitatory projections that facilitate reward learning (Stuber et al, 2011), and sends indirect projections back to the PFC (Cardinal, Parkinson, Hall, & Everitt, 2002; Casey, 2015; Cho, Ernst, & Fudge, 2013). The strong connectivity from the amygdala to the ventral striatum (Cho et al, 2013) has been observed during human development starting as early as early childhood as measured by resting state functional connectivity (Fareri et al, 2015). However, what will be clear in this review is that to date, the functional significance of these amygdala-ventral striatum connections has not been thoroughly examined in human development, and much of the extant human developmental work has approached the function of these two regions in parallel rather than in coordination.…”
Section: A Foreword On Stress and Adolescencementioning
confidence: 99%
“…Previous RS studies already observed developmental changes in functional connectivity between subcortical regions and prefrontal circuitry. Whereas the functional coupling between the amygdala and medial PFC has been found to increase (Gabard‐Durnam et al, ) or show minimal changes (Peters, Peper, Duijvenvoorde, Braams, & Crone, ) across adolescence, studies also found a developmental decrease in connectivity strength for other subcortical–cortical connections, such as connectivity between the ventral striatum and PFC (Fareri et al, ; Padmanabhan, Lynn, Foran, Luna, & O'Hearn, ; Porter et al, ; van Duijvenvoorde, Achterberg, Braams, Peters, & Crone, ). This decrease in functional coupling between subcortical and prefrontal circuitries has been interpreted as a maturation of brain networks, and linked to a developmental decrease in risky behavior and reward valuation (van Duijvenvoorde, Achterberg, et al, ) across adolescence, but also to individual differences in risky behavior.…”
Section: Introductionmentioning
confidence: 99%